A comparison of the 2008?2009 post-MINER Act safety performance of union and non-union underground coal mines. (28th November 2011) - Grayson, R.L.; Kinilakodi, H.
This study analyses the comparative safety performance between union and non-union mines for the period 2008?2009, following the 2006 MINER Act. Significant findings indicate that the Severity Measure for union mines was 54.9% and 32.1% higher than for non-union mines in 2008 and 2009, respectively; union mines had a lower no-days-lost incidence rate; and the non-fatal days-lost incidence rate for non-union mines was 8.5% and 20.5% lower than for union mines in 2008 and 2009. Union mines had higher fatality-disability (62.2% higher) and serious injury (43.3%) rates. Confounding variable effects on fatality and injury rates were examined for impact.